2010
DOI: 10.1248/cpb.58.381
|View full text |Cite
|
Sign up to set email alerts
|

Ylangene-Type and Nardosinane-Type Sesquiterpenoids from the Soft Corals Lemnalia flava and Paralemnalia thyrsoides

Abstract: Chemical investigations of the Formosan soft coral Lemnalia flava have obtained a new ylangene-type sesquiterpenoid, (1S,2S,4R,6S,7R,8S)-4a a-formyloxy-b b-ylangene (1), along with two known sesquiterpenoids, lemnalol (2) and isolemnalol (3). Three new nardosinane-type sesquiterpenoids, designated as paralemnolins J-L (4-6), and five known sesquiterpenoids (7-11), were isolated from the other soft coral Paralemnalia thyrsoides. The structures of metabolites 1 and 4-6 were elucidated through extensive spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…It was reported that a new ylangene-type sesquiterpenoid ( 32 ) was isolated from the Formosan soft coral L. flava [ 27 ] along with two related known ones, lemnalol ( 33 ) [ 28 ] and cervicol ( 34 ) [ 29 ]. It is worth mentioning that the parent hydrocarbon of ylangane is a stereoisomer of α -copaane as regards the orientation of the isopropyl group at C-8 ( α -orientation for ylangane, β -orientation for copaane) [ 30 ].…”
Section: Marine Natural Products From Lemnalia mentioning
confidence: 99%
“…It was reported that a new ylangene-type sesquiterpenoid ( 32 ) was isolated from the Formosan soft coral L. flava [ 27 ] along with two related known ones, lemnalol ( 33 ) [ 28 ] and cervicol ( 34 ) [ 29 ]. It is worth mentioning that the parent hydrocarbon of ylangane is a stereoisomer of α -copaane as regards the orientation of the isopropyl group at C-8 ( α -orientation for ylangane, β -orientation for copaane) [ 30 ].…”
Section: Marine Natural Products From Lemnalia mentioning
confidence: 99%
“…15 The reaction was found to be both stereo-and regioselective as seen from both spectroscopic data and X-ray crystallography. Previous attempts in our group to achieve ring expansion of compound 1 using protic acids like HCl, p-toluenesulfonic acid or CF 3 COOH, and Lewis acids like BF 3 , AlCl 3 , HgSO 4 , Hg(OAc) 2 or AgNO 3 were unsuccessful. 15 However, using 45 % HBr in acetic acid a near quantitative yield of a product corresponding to compound 5 was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, soft corals have become one of the most prolific sources for the discovery of novel secondary metabolites [ 1 ]. Previous chemical investigations on soft corals of the genus Lemnalia have led to the isolation and identification of variety of ylangene-derived sesquiterpenoids [ 2 , 3 , 4 , 5 ]. Some of these have been found to possess various biological activities, such as cytotoxic [ 4 ] and anti-inflammatory properties [ 6 ].…”
Section: Introductionmentioning
confidence: 99%